2020
DOI: 10.1186/s12931-020-01343-x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal epinephrine effects on epinephrine pharmacokinetics and heart rate in a nasal congestion canine model

Abstract: Background: Histamine release and vasodilation during an allergic reaction can alter the pharmacokinetics of drugs administered via the intranasal (IN) route. The current study evaluated the effects of histamine-induced nasal congestion on epinephrine pharmacokinetics and heart rate changes after IN epinephrine. Methods: Dogs received 5% histamine or saline IN followed by 4 mg epinephrine IN. Nasal restriction pressure, epinephrine concentration, and heart rate were assessed. Maximum concentration (C max), are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Administration of a single dose of neffy following NAC-induced allergic rhinitis resulted in an increase in the rate of epinephrine absorption. It is assumed that this increased absorption is due to the increased permeability in the nasal mucosa, as this phenomenon was observed in the anaphylaxis dog model and has been reported in the literature [ 49 , 50 ]. At the same time, neffy 2 mg with rhinitis also resulted in more rapid clearance compared with normal nasal conditions ( Figure 10 ).…”
Section: Review Of Neffy Datamentioning
confidence: 95%
See 2 more Smart Citations
“…Administration of a single dose of neffy following NAC-induced allergic rhinitis resulted in an increase in the rate of epinephrine absorption. It is assumed that this increased absorption is due to the increased permeability in the nasal mucosa, as this phenomenon was observed in the anaphylaxis dog model and has been reported in the literature [ 49 , 50 ]. At the same time, neffy 2 mg with rhinitis also resulted in more rapid clearance compared with normal nasal conditions ( Figure 10 ).…”
Section: Review Of Neffy Datamentioning
confidence: 95%
“…Although epinephrine is considered the only safe and effective first-line treatment of anaphylaxis [ 46 ], there have been reports of safety issues due to overdosing, both following manual IM administration and EAI administration [ 29 , 47 , 48 ]. For IN products, it has been reported that epinephrine absorption during an allergic reaction may be increased due to changes in vascular permeability [ 49 , 50 ]. A high dose of epinephrine in the presence of increased permeability in the nasal mucosa, due to an allergic reaction or population variability, could potentially result in excessive absorption and increase the risk of overdose [ 51 ].…”
Section: Neffy Product Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, drugs administered by the nasal route can directly reach the central nervous system (CNS) via the trigeminal and olfactory nerves (Erdo et al, 2018). The IN route of administration in dogs has been investigated for midazolam, dexmedetomidine, epinephrine, naloxone, and ketamine (Bleske et al, 1992; Charalambous et al, 2017; Charalambous et al, 2019; Dretchen et al, 2020; Santangelo et al, 2019; Tuttle et al, 2020; Vlerick et al, 2020; Wahler et al, 2019). These studies reported the intranasal route of administration to be clinically effective and/or results in adequate plasma concentrations of the investigated drug.…”
Section: Introductionmentioning
confidence: 99%